(untitled) (BIRDEM Medical Journal, 2014)
Despite all of our advances, women with epilepsy face obstacles when it comes to pregnancy and childbearing. Many of these obstacles are social, based on incorrect and inappropriate attitudes of the public towards persons with epilepsy. Most women with epilepsy can conceive and bear healthy children. They have higher probabilities of infertility but this is often amenable to treatment. Complications of pregnancy are higher and revolve primarily around the increased risk of maternal seizures. Careful monitoring of the clinical condition of the patient and the free anticonvulsant levels will obviate much of this difficulty. Maternal seizures themselves can pose hazards for women with epilepsy and their offspring and generalized convulsive seizures are clearly to be avoided. Adverse pregnancy outcomes tend to be seen more often in particular: congenital malformations, dysmorphic features, neonatal hemorrhage and fetal death. Neonatal and infant mortality is increased to two to threefold over the general population; and an uncertain risk of developmental delay particularly in the area of language acquisition. Risks can be reduced by ensuring good seizure control, monotherapy, preconceptual use of multivitamins with folate. The plethora of new anticonvulsants offers us new opportunities for improving the function and control of persons with epilepsy. All of the risks aside, the majority of women with epilepsy can and will have healthy children. DOI: http://dx.doi.org/10.3329/birdem.v4i1.18552 Birdem Med J 2014; 4(1): 38-42